Early childhood otitis media and later school performance – A prospective cohort study of associations. (March 2017) - Fougner, Vincent; Kørvel-Hanquist, Asbjørn; Koch, Anders; Dammeyer, Jesper; Niclasen, Janni; Lous, Jørgen; Homøe, Preben
Abstract: Introduction: Otitis media (OM) is a common disease in childhood and hearing loss (HL) is the most common complication. Prolonged HL may lead to language delay and cognitive difficulties. However, the consequences of HL due to OM are not fully understood. The aim of this study was to determine the possible association between number of OM episodes in childhood and self-rated school performance controlling for potential confounders. Methods: Prospectively gathered systematic interview data on OM episodes in early childhood and school performance at 11 years of age were obtained from The Danish National Birth Cohort, involving >100, 000 individual pregnancies and their offspring. We defined four exposure groups (0, 1–3, 4–6 and ≥7 OM episodes) and assessed general school performance, mathematics and literacy. Possible confounders were recognized à priori and associations were determined using proportional odds regression. Results: Out of 94, 745 successful pregnancies, 35, 946 children without malformations and their parents completed a questionnaire at age 11 years. No associations were observed between number of OM episodes and school performance, even in children with ≥7 OM episodes. Conclusion: This national birth-cohort study did not support the hypothesis that the number of OM episodes in childhood is associated with reduced self-reported school performance in children at 11 years of age.